2022
DOI: 10.1021/acs.accounts.2c00004
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Nature of Heterogeneous Electrofreezing of Supercooled Water Revealed on Polar (Pyroelectric) Surfaces

Abstract: Conspectus The ability to control the icing temperature of supercooled water (SCW) is of supreme importance in subfields of pure and applied sciences. The ice freezing of SCW can be influenced heterogeneously by electric effects, a process known as electrofreezing. This effect was first discovered during the 19th century; however, its mechanism is still under debate. In this Account we demonstrate, by capitalizing on the properties of polar crystals, that heterogeneous electrofreezing of SCW is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…We next look at the accuracy of the ML model trained on the revPBE0-D3 functional. We and others [3][4][5][6] have extensively used these revPBE0-D3 ML models to study the properties of bulk, interfacial and nanoconned water, and we observe high delity in predicting the thermodynamic and dynamical properties of revPBE0-D3 water.…”
mentioning
confidence: 69%
See 2 more Smart Citations
“…We next look at the accuracy of the ML model trained on the revPBE0-D3 functional. We and others [3][4][5][6] have extensively used these revPBE0-D3 ML models to study the properties of bulk, interfacial and nanoconned water, and we observe high delity in predicting the thermodynamic and dynamical properties of revPBE0-D3 water.…”
mentioning
confidence: 69%
“…I would also like to mention the work of two other participants attending this Faraday Discussions meeting, Leah Javitt and Prof. Meir Lahav, who have shown that various dissolved substances, including guanidinium chloride, aluminium ions and magnesium ions can promote ice nucleation on pyroelectric surfaces. 6 It is my view that this is probably a rather different ice nucleating system from feldspar and other atmospherically relevant substances, but that comparison between the different systems may at some stage prove revealing.…”
Section: Susanmentioning
confidence: 97%
See 1 more Smart Citation
“…Last but not the least, we also compare the studies performed in recent years on promoting water freezing with an electric field to guide follow-up research or industrial design. Pioneering research conducted by Lahav et al 51 demonstrates that electrofreezing on the polar crystal is a chemical process affected by the electric field and specific ions. Another significant research by Peleg et al 52 shows that electrofreezing is also influenced by the surface charge and electric field.…”
Section: Analysis Of Energy Consumption Duringmentioning
confidence: 99%